Лінгвістичне потрактування категорії сакрального (сакруму) - Піддубна, Н.В. (Мовознавство, 2019)
Стаття присвячена розглядові особливостей лінгвістичного потрактування категорії сакрального, яку розуміємо широко й уключаємо до неї корелят — поняття «профанум» (profanum). Акцентується увага на динамічному характері й взаємопереході понять зі сфери сакрального у сферу профанного, що відображено в процесах сакралізації, десакралізації, ресакралізації, які сприймаються як потужний засіб розвитку мови, зокрема її лексики й фразеології. The article is aimed at the analysis of the peculiar linguistic interpretation of the category of the sacred. The term «the sacred» used to belong to other humanitarian sciences. It is natural that within the domain of modern polyparadigmatic studies linguistics borrows terms from related disciplines, religious studies and theology, in particular. This process is predetermined by the actual expression of the category of the sacred in the language, and as a result, by the active studies of the verbalization of this category. The term «the sacred» was introduced into linguistics after its reterminalization and generalization. The notion of the sacred appears in demand in linguistics only in the late 90s of the20th century; it is mostly used in the works devoted to lexis and phraseology of Biblical origin and in the studies of Biblical texts and religious discourse. In this article, the attention is paid to the dynamic nature and variability of the category of the sacred, to the possibility to render sacred semantics by the system of verbal and non-verbal symbols. The author of the article interprets the category of the sacred in the broad sense, including the notion of the profane that correlates with it as far as non-sacred notions may become sacred and,vice versa, sacred ones may secularize (become profane). Involvement of the category of the sacred to linguistic sallows deeper and more thorough description and explanation of language phenomena realized in speech. Processes of sacralisation — desacralisation (secularization, profanation) are important for linguistics and for the development of a language in general. Namely, the development of polysemy is the most eloquent evidence of close relation of the profane and sacred spheres in language. Sacralisation of this or that notion causes appearance of new metaphorical meanings, creation of a variety of religious terms; desacralisation also widens semantics of a word and spheres of its use that is revealed in the processes of desemantisation of religious nominations on metaphorical or metonymic bases. These processes prove the dynamic character of the category of the sacred in modern cultures and, as a result, in languages, and become a powerful motif of their development and model the system of pragmatic effects, creating language games, evaluative senses, emotivity and figurativeness.